Antibacterial activity in local c. Odorata / Siti Norhidayati Saidi - Saidi, Siti Norhidayati (Faculty of Applied Sciences, 2014)
Chromolaena odorata (formerly known as Eupatorium odoratum) is one of herb with properties that are beneficial to human. Locally known as “Pokok Kapal Terbang” by Malaysians, this plant is one of the most invasive weed present in the country. The aim of this study is to evaluate the antibacterial activity possesses by the fresh leaves of local C. odorata. Methanol and ethanol crude extracts of this plant leaves were prepared and tested against two Gram-positive bacteria; Bacillus subtilis and Micrococcus luteus as well as Gram-negative bacteria; Pseudomonas aeruginosa and Escherichia coli by disc diffusion method. This study proved that fresh leaves of C. odorata was successfully extracted by both solvent due to the establishment of inhibition zone and ethanol was the best solvent to be used for fresh leaves sample extraction method. Besides, it was found that Gram-positive bacteria, B. subtilis are more susceptible toward the crude extract compared to other bacteria.